Agonistic security: Transcending (de/re)constructive divides in critical security studies - Tulumello, Simone (2020)
This article is a contribution to transcending the dichotomy between deconstruction and reconstruction in critical security studies. In the first part, I review dominant (Western/liberal) logics of security and the main strands of critical security studies to argue for the need to: overcome the liberal framework of the balance among rights and freedom, with its inherent imbrication with the fantasy of absolute security; and, contra the ultimate conclusions of deconstructive critique, to take the desire for security seriously at the same time. By advocating for embracing the tensions that surface at this intersection, I then move to my reconstructive endeavor. I set out a meta-theory with both analytical and normative nature, agonistic security, inspired by the political theory developed by Mouffe and Laclau. Building on the opposition between antagonism and agonism, I argue that security belongs to the “political”, and that it constitutes a field of struggle for politicization. I then argue for three conceptual shifts, which concretely define agonistic security: i) from an absolute/static to a relational/dynamic understanding of security; ii) from universalism to pluralism at a world scale; and iii) from the dominance of individual rights in Western/liberal thinking toward security as a collective endeavor. In conclusion, I take a step back and discuss the implications of agonistic security for the role of critique in security studies.